The Impact of COVID-19 on College Student Perceptions of Learning and Class Grades. Issue 11 (2nd November 2022) - West, Matthew
ABSTRACT: Although community college students have historically been at the forefront in utilizing some distance education across their degrees due to their own employment, parenting, or transportation circumstances, COVID-19 forced all college instruction online for much of the 2020–2021 year in Alabama. Given the economically and technologically precarious situation for many community college students in the state, such a radical change in course delivery proved to be a challenge for many to cope with. This study examined such pandemic-related difficulties by studying how students perceived changes in their learning and grades as a result of this instructional shift. Students at an urban, medium-sized, predominantly black community college (PBCC) in Alabama ( n = 204) were surveyed in the Fall 2020 semester to determine if they felt COVID-19 circumstances had caused their grades and/or learning to suffer. Results indicated students felt they had earned better or the same grades as before COVID when they had more access to a computer in general, a computer specifically with better capacity, wi-fi, a study place, a cell phone, and a textbook, as well as having attended class better. In particular, having a computer with sufficient capacity was over three times as important as other resources in determining better student perceptions of grades. Possessing an adequate computer was more important to perceived grades than student background characteristics, having a high grade point average, and even strong study habits. Due to changes in perceived learning, statistically significant predictors included age and class attendance.